Second International Islamic Conference on Prevention of Drugs and Alcohol: Islamabad, Pakistan Shawwal 26-28 1409/June 1-3, 1989 (American Journal of Islam and Society, 1989)
More than four hundred scholars and guests from around the worldattended the "Second International Islamic Conference on Prevention of Drugsand Alcohol" held at the International Islamic University, Islamabad, PakistanShawwal 26-28 1409/June 1-3, 1989.The conference, sponsored by Rabita al-Alam al-Islami, Makkah alMukarramah(World Muslim League), and the IIU in Islamabad, re-affim1edthe commitment of the Muslim Ummah to elirnfoate the threat and menaceof drugs and alcohol in Islamic states and societies world-wide.Scholars attending the conference represented both the natural and socialsciences, and individual professions ranged from medical doctors and lawenforcement authorities to social engineers and Islamic authorities in Seerahand Shariah. More than 70 scholars presented papers on critical aspects ofthe problem. The conference agenda embraced six major concerns:l) The Nature and Extent of Drug Abuse.2) Biological Mechanism.3) Religious and Educational Outlook.4 ) Social Context of Drug Abuse ...